Studi Kelayakan Tanaman Rasau (Pandanus helicopus ) Sebagai Bahan Baku Papan Partikel : Feasibility Study of Rasau Plant (Pandanus helicopus) As Raw Material for Particle Board - Koroh, Desy Natalia; Saputera, Saputera; Jemi, Renhart; Santoso, Mahdi (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2024)
The rasau plant grows in riparian forest areas within tropical peat swamp forests. It is a lignocellulosic material with potential as a raw material for particleboard. Before being used as a raw material, a feasibility study must be conducted on the rasau plant (Pandanus helicopus). The stems of rasau were analyzed for cell dimensions, cell proportions, chemical composition, and physical and mechanical properties. The results indicate that the fiber dimensions and proportions, as well as the physical and mechanical properties, demonstrate that rasau stems are suitable for use as a raw material for non-structural particleboard. Rasau can be utilized as a raw material for particleboard, provided the particles undergo cold water soaking and use phenol-formaldehyde or melamine-formaldehyde resin adhesives, followed by hot pressing